Analisis Gaya Kepemimpinan Guru pada Aspek Pedagogik Berdasarkan Pengalaman Kerja di Sekolah Dasar Kota Mataram - Orance A. N. Nuban; Retno Apriliyani; Reni Rohmayani; Hijratul Arifin; Nisa Agustina (JPAP (Jurnal Praktisi Administrasi Pendidikan), 2025)
This research aims to analyze teacher leadership styles in pedagogical aspects based on work experience in Mataram City Elementary Schools using a quantitative approach. The research population consisted of 146 elementary schools, with a total of 16 respondents participating in this study. Data collection was carried out through distributing questionnaires designed to collect information regarding teacher leadership styles in pedagogical aspects. Data analysis was carried out using descriptive statistics to determine the significant relationship between the independent variable (leadership style) and the dependent variable (pedagogical aspects). The research results show that the teacher's leadership style in the pedagogical aspect is based on work experience in elementary schools in Mataram City, including; 1) Transformational leadership style; 2) Instructional leadership style; 3) Authentic leadership style; and 4) Collaborative leadership style. Teachers with 0-10 years of service are more likely to consistently apply a collaborative leadership style than teachers with more than 10 years of service.